2013
DOI: 10.1002/jso.23424
|View full text |Cite
|
Sign up to set email alerts
|

The combined use of the neutrophil-lymphocyte ratio and C-reactive protein level as prognostic predictors in adult patients with soft tissue sarcoma

Abstract: We recommend the routine measurement of these markers to identify patients with a greater risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 13 publications
5
53
0
1
Order By: Relevance
“…NLR may occasionally not be a tumour-specific marker because other inflammatory conditions and steroid treatments could be confounding factors. Some authors have suggested that NLR should be assessed together with other inflammatory markers such as CRP (Nakamura et al , 2013; Yalcinkaya et al , 2013). In addition, numerous articles have reported on NLR using different cutoff levels that require validation.…”
Section: Discussionmentioning
confidence: 99%
“…NLR may occasionally not be a tumour-specific marker because other inflammatory conditions and steroid treatments could be confounding factors. Some authors have suggested that NLR should be assessed together with other inflammatory markers such as CRP (Nakamura et al , 2013; Yalcinkaya et al , 2013). In addition, numerous articles have reported on NLR using different cutoff levels that require validation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of 2 biomarkers may increase the predictive ability of individual markers in AMI patients with multiple comorbidities. In previous studies, performed in other disease entities such as cancers, the combined use of NLR and CRP level was found to be helpful for predicting survival 7). It was found that patients with both an elevated CRP level and high NLR had a poorer survival rate than those with either an elevated CRP level or high NLR.…”
Section: Introductionmentioning
confidence: 95%
“…Comorbid inflammatory conditions and steroid treatments can confound results. Some authors recommend that these ratios be assessed with other inf lammatory markers such as C-reactive protein, red cell distribution width, and erythrocyte sedimentation rate 25,26 . Validation remains an ongoing consideration because numerous articles have reported on nlr and mlr using different cut-off levels [27][28][29][30] .…”
Section: Figure 2 Kaplan-meier Curves For Overall Survival By Neutropmentioning
confidence: 99%